1995
DOI: 10.1017/s0022029900031332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of proteolytic activities in various lactobacilli

Abstract: SUMMARYA total of 169Lactobacillusstrains from 12 species (Lb. acidophilus, Lb. brevis, Lb. buchneri, Lb. casei, Lb. delbrueckiisubsp.bulgaricus, Lb. delbrueckiisubsp.delbrueckii, Lb. delbrueckiisubsp.lactis, Lb. fermentum, Lb. helveticus, Lb. paracasei subsp. paracasei, Lb. plantarum and Lb. rhamnosus), isolated from raw milk and various milk products, and 9Lactococcus lactisstrains were evaluated for peptidase activities with five chromogenic substrates and a tryptic digest of casein. Within each species, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
5
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 35 publications
4
70
5
1
Order By: Relevance
“…Afterward, L. casei, L. rhamnosus, and B. lactis were placed, respectively. L. acidophilus and L. casei have high proteolytic activities (Sasaki et al 1995) that improve their acidification rate. Proteolytic activities of probiotics are directly proportional to their acidification rate (Azcarate-Peril et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, L. casei, L. rhamnosus, and B. lactis were placed, respectively. L. acidophilus and L. casei have high proteolytic activities (Sasaki et al 1995) that improve their acidification rate. Proteolytic activities of probiotics are directly proportional to their acidification rate (Azcarate-Peril et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cells counts on FH medium did not decrease during incubation, but it could hide a viability decrease of some strains among the population, as already observed in cheese [8]. FHL possess high autolytic activity [3,12] and peptidase activity [33,38]. The raw milk flora of Swiss-type cheese, composed of FHL and PAB has been shown to generally increase proteolysis indexes during ripening, i.e.…”
Section: Discussionmentioning
confidence: 67%
“…delbrueckii and ssp. lactis [33]. Lysis of L. casei and L. plantarum has not yet been extensively studied but was close to L. helveticus under conditions prevailing in cheese [12].…”
Section: Introductionmentioning
confidence: 99%
“…The overall proteolytic activity of lactobacilli has been found to be higher than that of Lc. lactis because lactobacilli possess additional peptidases and because their peptidases have higher expression levels [21,38]. Also, Str.…”
Section: Effect Of Type Of Culturementioning
confidence: 99%
“…They concluded that, perhaps, the effects of lactobacilli are not the same in cow's milk cheese as in ewe's milk cheese. Sasaki et al [38] found that strains of Lb. paracasei ssp.…”
Section: Effect Of Type Of Culturementioning
confidence: 99%